Fundamentals of Entrepreneurship (ENT300) : Mira cake house / Jenickson Juan … [et al.] - Juan, Jenickson; Merdicken, William Nichole; Abdul Wahab, Noraishah; Jaafar, Farizah Syahirah; Wan Zainal Abidin, Sharifah Aisah; Mading, Stephenie (2018)
Mira Cake house is one of leading cake baking business in Sarawak centered at Kampung Boyan Kuching. It covers wide range of customers and clients from various states and tourists from other country. The company offer unique type of Kek Lapis Sarawak which is known as Kek Lapis Basah. The difference taste of Kek Lapis at Mira Cake House compare to other regular Kek Lapis company are the moistness of the cake . Other than that, they also produce food that are popular in Sarawak which is 'Kuih Cincin', biscuits , Laksa Sarawak and many more.